2016
DOI: 10.1016/j.atherosclerosis.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Lipid lowering drug therapy in patients with coronary heart disease from 24 European countries – Findings from the EUROASPIRE IV survey

Abstract: Too many CHD patients with dyslipidaemia are still inadequately treated and most of these patients on statin therapy are not achieving the treatment targets. Therapeutic control of LDL-C is clearly related to the intensity of lipid lowering drug regimen after the CHD event indicating that a considerable potential still exists throughout Europe to reduce CHD mortality and morbidity rates through more efficient LDL-C lowering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
128
3
28

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 38 publications
8
128
3
28
Order By: Relevance
“…13 Other authors suggested several reasons for the mediocre response during statin therapy: inadequate dose, non-adherence to prescribed dose, statin resistance and / or intolerance, and side effects. 14,15 However, our results confirm the association between increased LDL-c levels with cardiovascular event rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Other authors suggested several reasons for the mediocre response during statin therapy: inadequate dose, non-adherence to prescribed dose, statin resistance and / or intolerance, and side effects. 14,15 However, our results confirm the association between increased LDL-c levels with cardiovascular event rates.…”
Section: Discussionmentioning
confidence: 99%
“…Reiner et al 13 emphasized the need to reduce LDL-c levels after a cardiovascular event to reduce coronary heart disease mortality and morbidity. 13 Other authors suggested several reasons for the mediocre response during statin therapy: inadequate dose, non-adherence to prescribed dose, statin resistance and / or intolerance, and side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В России этот пока-затель составил 15,9%. Наилучшие показатели продемонстрировала Испания -41% [20].…”
unclassified
“…So kann trotz maximaler Statindosis und Kombination mit Hemmstoffen der enteralen Cholesterinaufnahme (Ezetimib, Ionenaustauscherharze) bei Hochrisikopatienten keine klinisch ausreichende LDL-Senkung erreicht werden [3]. Ein Grund hierfür liegt in der Variabilität des Ansprechens der Patienten auf Statine.…”
unclassified